Antiproliferative and antioxidant potentials of bioactive edible vegetable fraction of Achyranthes ferruginea Roxb. in cancer cell line. Issue 7 (1st June 2021) - Reza, A. S. M. Ali; Haque, Md. Anwarul; Sarker, Joy; Nasrin, Mst. Samima; Rahman, Md. Mahbubur; Tareq, Abu Montakim; Khan, Zidan; Rashid, Mamunur; Sadik, Md. Golam; Tsukahara, Toshifumi; Alam, AHM Khurshid
Abstract: In the present study, the aerial parts of Achyranthes ferruginea underwent investigation of their in vitro antioxidant and free radical‐scavenging activities in cell‐free conditions, their phytoconstituents using gas chromatography‐mass spectrometry (GC‐MS), and their cytotoxic activity in HeLa cells. A. ferruginea was extracted with 80% methanol and successively fractionated with solvents to yield petroleum ether (PEF), chloroform (CHF), ethyl acetate (EAF), and aqueous (AQF) fractions. GC‐MS analysis revealed that CHF contained ten phytoconstituents, including different forms of octadecanoic acid methyl esters. The total antioxidant and ferric‐reducing antioxidant capacities of the extracts and the standard catechin (CA) were as follows: CA >CHF >PEF >CME (crude methanolic extract) >EAF >AQF, and CA >CHF >EAF >PEF >AQF >CME, respectively. CHF showed the highest DPPH‐free radical‐scavenging activity, with a median inhibitory concentration of 10.5 ± 0.28 µg/ml, which was slightly higher than that of the standard butylated hydroxytoluene (12.0 ± 0.09 µg/ml). In the hydroxyl radical‐scavenging assay, CHF showed identical scavenging activity (9.25 ± 0.73 µg/ml) when compared to CA (10.50 ± 1.06 µg/ml). Moreover, CHF showed strong cytotoxic activity (19.95 ± 1.18 µg/ml) in HeLa cells, which was alike to that of the standards vincristine sulfate and 5‐fluorouracil (15.84 ± 1.64 µg/ml and 12.59 ± 1.75 µg/ml, respectively). The in silico study revealed that identified compounds were significantly linked to the targets of various cancer cells and oxidative enzymes. However, online prediction by SwissADME, admetSAR, and PASS showed that it has drug‐like, nontoxic, and potential pharmacological actions. Abstract : In this study, we found that the CHF of A. ferruginea has strong antioxidant and cytotoxic properties in different cell lines. GC‐MS quantitative phytochemical screening revealed that CHF contains 10 compounds which has known cytotoxic activity. Therefore, the obtained biological activity of A. ferruginea supports its use as a traditional medicine against different illnesses, and the plant can be considered a potential candidate for treating cancer.